Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jcmgh.2021.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Population-Specific Cell Subsets in Chinese Ulcerative Colitis Patients Using Single-Cell RNA Sequencing

Abstract: Background & Aims Genome-wide association studies (GWAS) and transcriptome analyses have been performed to better understand the pathogenesis of ulcerative colitis (UC). However, current studies mainly focus on European ancestry, highlighting a great need to identify the key genes, pathways and cell types in colonic mucosal cells of adult UC patients from other ancestries. Here we aimed to identify key genes and cell types in colonic mucosal of UC. Methods We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
3
14
0
Order By: Relevance
“…Importantly, transcripts elevated in goblet cells ( Figure 2 ) were in agreement with the subsequent study by Li et al ( 35 ), including MUC2, ITLN1, REP15, LRRC26, NPDC1, TPSG1, SERPINA1, CLCA1, and SPINK4.…”
Section: Goblet Cellssupporting
confidence: 91%
See 3 more Smart Citations
“…Importantly, transcripts elevated in goblet cells ( Figure 2 ) were in agreement with the subsequent study by Li et al ( 35 ), including MUC2, ITLN1, REP15, LRRC26, NPDC1, TPSG1, SERPINA1, CLCA1, and SPINK4.…”
Section: Goblet Cellssupporting
confidence: 91%
“…In UC-affected epithelium ( Figure 2 ), only SCD, RNASE1, and ASRGL1 were concordant with goblet cell findings by Li et al ( 35 ).…”
Section: Goblet Cellssupporting
confidence: 87%
See 2 more Smart Citations
“…These findings can provide new ideas for the diagnosis and treatment of intestinal diseases[ 7 ]. Li et al [ 8 ] found that UC risk-related genes are enriched in progenitor cells, glial cells and immune cells and showed consistently altered expression in immune cells of both inflammatory and noninflammatory tissues, whereas drug target genes were differentially expressed in antigen-presenting cells. T helper 17 (Th17)-cell activation was observed in both the epithelial cell lineage and immune cell lineage of UC patients, indicating systematic changes in Th17-driven immune activity.…”
Section: Introductionmentioning
confidence: 99%